Implementation of the Midtrans Payment Gateway in a Web-Based School Payment Information System Using a Design Thinking Approach (Case Study at Smp Pelita Nusantara) - Ishfy Achmed Mahessa; Asep Muhidin; Irfan Afriantoro (Indonesian Journal of Business Analytics, 2024)
The rapid development of technology can help the education sector with the existence of information systems in an educational institution, especially in the process of paying student school fees. Pelita Nusantara Middle School is one of the schools that is still conducting administrative activities payment of education costs by recording manuals. This certainly takes a long time and causes long queues and sometimes errors often occur in reporting reports. This research was made to overcome these problems using the Design Thinking approach through several stages which included the empathize, define, ideate, prototype, and testing stages. The process of making information systems payment of this education fee, the authors designed it using the PHP and MySQL programming language as a database design. The results obtained from this study are the application of website -based education fees payment with the application of Midtrans Payment Gateway. The conclusion obtained from this study is that the application facilitates the payment process at Pelita Nusantara Middle School to be more effective and efficient and save a lot of time.